Persicaria minor F-box gene PmF-box1 indirectly affects Arabidopsis thaliana LOX-HPL pathway for green leaf volatile production - Nur-Athirah Abd-Hamid,; Muhammad Naeem-Ul-Hassan,; Zamri Zainal,; Ismanizan Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Green leaf volatiles (GLVs) play an essential role in plant defence, plant-plant interaction and plant-insect interaction. The plant releases GLVs and inhibits the growth and propagation of plant pathogens. In this study, overexpression of PmF-box1 in wild type A. thaliana showed the downregulation of genes involved in the lipoxygenase-hydroperoxide lyase (LOX-HPL) pathway, which contributes to the biosynthesis of GLVs. It resulted in a marked reduction of hexanal production in the PmF-box1-overexpressing plant. The expression pattern of LOX-HPL branch genes in the kelch-repeat modified PmF-box1 (KMF)-overexpressing plant showed a pattern much closer to the expression of LOX-HPL branch genes in the vector control (VC) plant. It was shown that the functional KMF protein sequence was not responsible for the significant reduction of all GLVs including hexanal, 1-hexanol, (Z)-3-hexen-1-ol, and the carbon 5 (C5) volatile, 1-penten-3-ol, in plants overexpressing KMF. Furthermore, this study also showed that the relative proportion of production of 1-penten-3-ol to hexanal was higher in the PmF-box1-overexpressing plant. Based on the current comparative literature search, PmF-box1 does not appear to interact directly with the proteins or transcription factors of the LOX-HPL pathway. On the other hand, PmF-box1 interacts with SAMS1, which subsequently influences the HPL pathway enzyme genes. Thus, this study highlights the potential roles of PmF-box1 in the manipulation of GLV productions.